An Experimental Vignette Study of How Supervisor Developmental Feedback and Psychological Safety Influence Intention to Innovative Work Behavior in Education Technology Company - Shabrina, Devika Nur; Etikariena, Arum (JURNAL PSIKOLOGI, 2024)
This study examines the influence of supervisor developmental feedback (SDF) and psychological safety (PS) on the intention to engage in innovative work behavior in educational technology (EdTech) companies in Indonesia through experimental vignette method (EVM). The participants of this study consisted of 287 employees from EdTech companies in the Jabodetabek area. Participants were provided with hypothetical scenario to form perceptions of manipulated scenarios. Data were collected using an Indonesian version of the intention to innovative work behavior scale after reading the hypothetical scenario. Descriptive statistical techniques and factorial ANOVA were used for data analysis. The results indicate that SDF significantly predicts intention to engage in innovative work behavior (F(1, 283)=27.86; p=.00). Similarly, PS also significantly predicts intention to innovative work behavior (F(1, 283)=164.41; p=.00). However, the interaction between SDF and PS does not have a significant effect on the intention to innovative work behavior (F(1, 283)=.74; p=.39). Understanding the influence of SDF and PS on innovative work behavior (IWB) can assist supervisors in creating a psychologically safe environment and providing developmental feedback to enhance employees' intention to engage in innovative work behavior.